Factors affecting amount of water offered to dairy cattle in Kiambu District and their effects on productivity. - Muli, A.N. (University of Nairobi, 2000)
To study the factors affecting amount of water offered to dairy cattle and their effects on productivity, 20 smallholder dairy farmers in Kiambu District were randomly selected. Data collected once fortnightly for 11 months was analysed to study the impact of water on offer on productivity. Data was collected on source of water (on- or off-farm), water storage, distance to water source (categorised as 1) 0-200m, 2) 200-1000m or 3) >lkm), watering frequency (continuous or non-continuous watering), mode of presentation (categorised as water troughs of 1 « 100), or 2 (> 100 litres)), means of water transport categorised as none needed. manual, or carts/wheelbarrows/donkeys/bicycles. Total amount of feed offered, water offered. milk yield, live weight and condition score were also monitored. Mean amount of water offered per farm per day was 134 I. or 35.6 11300kg LWI day. However, the variability was high (range of 7 - 108 11300kg LW/day). Of the farms surveyed, 60% had on-farm water source, which was within a radius of 200m. 40% trekked between 0.2 - 2.5km to fetch water for livestock. Only 25% had water piped directly to the water trough. 55% carried water manually by bucket while 20% used draught power or bicycle or wheelbarrows to transport water. Small water troughs (20-1- buckets) were used in 25% of the farms surveyed to water dairy cattle. 50% of the farms practised non-continuous watering and 55% had no water storage facilities. Analysis of the data showed that source, distance to source, water transport means, water storage facilities, watering frequency, volume of water trough significantly affected the amount of water offered/day to dairy cattle (P<0.05). Distance to water source was related to quantity of water offered. with mean quantities of 43. 23 and 21 1/300kg LW being offered to animals in the distance categories 1-3 cited above. Cows with on-farm water source received 43 1compared to 22 1offered in farms with off-farm water source. Mean quantities of 52. 30 and 25 1/300 kg lwt were offered to dairy cattle in farms with water piped directly to water trough, manual-hand bucket and those using draught/bicycle/wheelbarrow respectively. Watering frequency influenced water on offer with mean quantities of 491/300 kg lwt/day (continuous watering) and 21-1/300 kg lwt/day (non-continuous watering). Small water troughs restricted the amount of water on offer/day (21 1I300 kg lwt) compared to 39 1I300 kg 1wt /day offered in farms with large water troughs. Dairy cows were offered a variety of feeds. Napier and other types of grasses were the main feeds constituting more than half (1.581100 kg lwt) of the total feed offered. Dry maize stover was second to napier/grasses in importance with an average of 0.567 kg / 100 kg lwt per day. Concentrates were offered in all farms to lactating cows at an average of 0.4855 kg /100 kg lwt per day. These included commercial dairy meal, cotton seed cake, bone meal, maize bran. maize germ. wheat bran and poultry litter. It was observed that dairy cattle in farms with on-farm water source, large water troughs, practicing continuous watering and those with water storage facilities were offered high amounts of water and produced significantly (P<0.05) more mille In addition, these farms were offered high amounts of concentrates and napier grass. In farms where high amount of dry maize stover was offered to dairy cattle, coupled with low water on offer, low milk yields were realised. This was observed in farms with small water troughs, offfarm water source and farms without piped water. General linear model analysis of the data indicated that the amount of water offered (l/300kg LW/day), age, parity, body weight stage of lactation, body condition score and dry matter on offer had a significant effect on milk yield. Increasing amount of water offered increased milk yield. In conclusion. high amount of water. concentrates and napier/grass on offer resulted in high milk yields. These results highlight the increasing importance of ensuring adequate provision of drinking water as milk yields in dairy cows increase. In this context smallholder dairy farmers in Kiambu District should be advised to increase the amount of water offered to dairy cattle from the average 35 litres/300 kg LW/day currently offered to at least the recommended 60 litres per day ..